Real-life monocentric experience of venetoclax-based regimens for acute myeloid leukemia - Sciumè, Mariarita; Bosi, Alessandro; Canzi, Marta; Ceparano, Giusy; Serpenti, Fabio; De Roberto, Pasquale; Fabris, Sonia; Tagliaferri, Elena; Cavallaro, Francesca; Onida, Francesco; Fracchiolla, Nicola Stefano (Frontiers in Oncology, 2023)
Introduction Combination of venetoclax and hypomethylating agents (HMAs) has become a standard of care in acute myeloid leukemia (AML) aged >75 years or who have comorbidities that preclude intensive induction chemotherapy. Methods We conducted a monocentric retrospective analysis on adult patients affected by treatment-naïve AML not eligible for standard induction therapy or refractory/relapsed (R/R) AML treated with venetoclax combinations outside clinical trials. Venetoclax was administered at the dose of 400 mg/daily after a short ramp-up and reduced in case of concomitant CYP3A4 inhibitors. Results Sixty consecutive AML were identified. Twenty-three patients (38%) were affected by treatment-naïve AML and 37 (62%) by R/R AML. Median age was 70 years. Among R/R AML 30% had received a prior allogeneic stem cell transplantation (allo-HSCT). In combination with venetoclax, 50 patients (83%) received azacitidine. Antifungal prophylaxis was performed in 33 patients (55%). Overall response rate was 60%, with 53% of complete remission (CR; 78% for treatment-naïve and 49% for R/R, p 0.017). Median overall survival was 130 days for R/R patients and 269 days for treatment-naïve patients; median event free survival was 145 days for R/R cohort and 199 days for treatment-naïve AML. Measurable residual disease was negative in 26% of evaluable patients in CR/CR with incomplete hematologic recovery after 2 cycles and in 50% after 4 cycles, with no significant association with survival. Eleven patients (18%) received an allo-HSCT after venetoclax combinations. Most common grade 3/4 adverse events were infectious (51% of the patients), or hematological without infections (25% of the patients). Use of CYP3A4 inhibitors was associated with a trend to shorter cytopenias and with a lower rate of infections. Invasive fungal infections were less frequent among patients receiving azole prophylaxis (6% vs 26%; p 0.0659). Discussion Venetoclax-based regimens are a viable option for AML considered not eligible for standard induction therapy and a valid rescue therapy in the R/R setting. Azole prophylaxis did not significantly affect response and it was associated with a lower rate of invasive fungal infections. Despite a limited number of patients, the association of venetoclax and HMAs proved to be also a feasible bridging therapy to transplantation.